2020
DOI: 10.1002/pca.2998
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic assay for the detection of kwakhurin and its application for the identification of Pueraria candollei var. mirifica (Airy Shaw & Suvat.) Niyomdham

Abstract: Introduction: The plant Pueraria candollei var. mirifica (Airy Shaw & Suvat.) Niyomdham (PM), known by its common Thai name as white Kwao Krua, is sometimes misidentified because it presents similar botanical characteristics to those of Butea superba (red Kwao Krua). The phytochemicals in PM are phytoestrogens in the class of isoflavonoids, but Butea superba contains flavonoids that exhibit androgenic and antiestrogen effects.Objectives: This research aims to develop a simple analytical method for identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
2
6
0
Order By: Relevance
“…The LOD of LFIA using mAbs for kwakhurin and miroestrol was reported to be 160 ng/mL and 1000 ng/mL, respectively. 15,26 The LOD observed for this strip was similar to that in earlier investigations.…”
Section: Lfia Testing and Detection In Plant Samplessupporting
confidence: 87%
See 1 more Smart Citation
“…The LOD of LFIA using mAbs for kwakhurin and miroestrol was reported to be 160 ng/mL and 1000 ng/mL, respectively. 15,26 The LOD observed for this strip was similar to that in earlier investigations.…”
Section: Lfia Testing and Detection In Plant Samplessupporting
confidence: 87%
“…This LFIA method could detect sennoside A, 13 sennoside B, 13 miroestrol, 14 and kwakhurin. 15 Additionally, the use of LFIA for a semi-quantitative study of artesunate has been reported. 16 This study aimed to generate a hybridoma clone that could secrete a GTG-specific mAb.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with carboxylic acid and hydroxyl functional groups are usually conjugated by a carbodiimidemediated reaction [33,34,47,[95][96][97][98][99][100][101][102], whereas compounds with active hydrogen, e.g., α-picolines, ketones, esters, and acetylenes, can be conjugated to an amine or amide group of the carrier by a Mannich reaction [103,104]. Furthermore, structure modifications of the parent compounds to add the reactive functional group to the molecule can be conducted when necessary.…”
Section: Production Of Hapten-carrier Moleculesmentioning
confidence: 99%
“… [ 47 ] Aconitine Alkaloid Aconitum spp. [ 29 ] Rhein Anthraquinone Rheum officinale [ 42 ] Kwakhurin Isoflavonoids Pueraria mirifica [ 102 ] Higenamine Benzyltetrahydroisoquinoline alkaloid Aconitum carmichaelii, Asarum heterotrophies, Nandina domestica [ 34 ] Amarogentin Secoiiridoid glycoside Swertia spp., Gentiana spp. [ 46 ] Colchicine Alkaloid Colchicum autumnale [ 44 ] …”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we focused on Kwa as a marker compound for standardization as it is a phytoestrogen [ 13 ] produced solely by P. candollei . We also developed various immunoassays for the determination of Kwa in P. candollei -derived products [ 15 , 16 , 17 , 18 ] as immunoassays enable sensitive and selective analyses of small molecules [ 19 , 20 ]. However, an animal-based approach is necessary for the production of antibodies used in immunoassays.…”
Section: Introductionmentioning
confidence: 99%